Anti-convulsant potential of quinazolinones. Issue 50 (5th May 2016) - Patel, Harun M.; Noolvi, Malleshappa N.; Shirkhedkar, Atul A.; Kulkarni, Abhijeet D.; Pardeshi, Chandrakantsing V.; Surana, Sanjay J.
Abstract : A series of novel quinazoline derivatives were virtually screened through different filters and evaluated for their anticonvulsant activity against electrically and chemically induced seizures. Abstract : A series of novel quinazoline derivatives were synthesized, virtually screened through different filters and evaluated for their anticonvulsant activity against electrically and chemically induced seizures, compared with that of the standard drugs methaqualone and sodium valproate. Compound48, 3-(2-aminophenyl)-7-chloro-2-phenylquinazolin-4(3 H )-one, was found to be the most potent compound of the series accompanied by relatively low neurotoxicity and low toxicity in the median lethal dose test as compared with the reference drugs. The obtained results showed that compounds12, 48, 49 and50 could be useful templates for future design, optimization, and investigation to construct more active analogs.